The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1997
DOI: 10.1088/0741-3335/39/3/004
|View full text |Cite
|
Sign up to set email alerts
|

Surface waves on the harmonics of the electron cyclotron frequency propagating along a plasma - metal interface

Abstract: Dispersion properties of slow electromagnetic surface waves propagating on the harmonics of the electron cyclotron frequency across the external steady magnetic field are studied in the case when the magnetic field is parallel to the plasma-metal interface. Theoretical investigation of these surface modes is carried out using the kinetic description under the condition of weak plasma spatial dispersion, when the radii of the charged plasma particles' Larmor rotation are much less than the spatial scale of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…(4) can be taken into consideration only for the calculation of the SWCF damping rates. Expressions for the Q11, Q l 2 , Q22 are presented in [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(4) can be taken into consideration only for the calculation of the SWCF damping rates. Expressions for the Q11, Q l 2 , Q22 are presented in [13].…”
Section: Introductionmentioning
confidence: 99%
“…(3), using eq. (11) and expressions (12), (13), which are infered from the boundary conditions, we obtain the following infinite set of equations:…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion properties of these surface X modes (STXM) in a nonuniform plasma-filled metal waveguide with dielectric coating have been studied in [11]. It was found that ion and electron STXM have different dispersion properties and, in the case of a plasma-metal interface, they can propagate only in mutually opposed directions [12]. The directions of their propagation are determined by the orientation of the Larmor rotation of the corresponding charged plasma particles near the metal interface.…”
Section: Introductionmentioning
confidence: 99%
“…Radiofrequency (RF) and microwave gas discharges produced and sustained by surface modes can be utilized in semiconductor processing, in pumping laser media, in plasma production (Moisan and Pelletier 1992;Ferreira and Moisan 1993), etc. Ion cyclotron resonance heating (CRH) (Becoulet 1996) and electron CRH (Laqua et al 1997) are well known as widely used methods of additional plasma heating in fusion devices. RF or microwave energy launched by antenna systems is transformed via various conversion processes into energy of ion or electron cyclotron waves.…”
Section: Introductionmentioning
confidence: 99%
“…Lyssoivan et al 1996). Dispersion properties of electron STXM have been examined by Azarenkov et al 1997b) for the case of propagation along the plasma-metal interface. The case of ion STXM propagation along the plasma-metal interface was studied by Azarenkov et al 1997c).…”
Section: Introductionmentioning
confidence: 99%